RAILLIETINA SPP. INFECTION BIRDS IN MISSAN / SOUTHERN OF IRAQ - Huda Ghanim Dakhil; Ali Idan Al-Musaedi (Scholar Express Journals, 2022)
Raillietina spp. affects several types of birds such as pigeons and domestic birds. This cestoda is considered as pathogenic parasite, and caused nodular tapeworm disease . This work is the first in Missan governorate, a total of 25 ducks and 20 farm chicken from the Missan market and 30 wild pigeons were taken randomly from some farms at the period from July2020- July 2021. They were examined to search of Raillietina spp. in digestive canal. The current study recorded several infection in all types of birds under the study, it is registered 6 (24%) in ducks, 10(50%) in farm chicken and 20(73.3 %) in wild pigeons. The statistical analysis confirmed the presence significant differences between the birds under the study. The aims of this study to determine Raillietina spp. infections of the birds under the study in Missan/ Southern of Iraq.
Keywords: Raillietina; ducks; farm chicken; Missan